2012
DOI: 10.1108/10444061211218302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship conflict in supervisor‐subordinate dyads:a subordinate perspective

Abstract: Purpose -This paper aims to offer insights regarding antecedents and consequences of relationship conflict in supervisor-subordinate dyads, regardless of the demographic characteristics of the dyads. The authors explain the causes and outcomes of relationship conflict utilizing an affective approach, and suggest that factors such as moods, values, and situational context play an important role in influencing relationship conflict and its outcomes -intention to quit and trust in supervisor. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 104 publications
3
39
0
Order By: Relevance
“…Such conflicts over goals, processes and personality differences are termed as task conflict, process conflict and relationship conflict respectively (Jehn, Greer, Levine, & Szulanski, 2008;Vaux& Kirk, 2018). Previous studies have reiterated that conflicts over personality and value differences which are termed as -relationship conflicts are detrimental for individuals and organisations alike (Hagemeister & Volmer, 2018;Ismail, Richard, & Taylor, 2012;Volmer, 2015;Li et al, 2020). However, in the conflict research, studies differ about the effect of task conflict on employee well-being and process conflict have been omitted from conflict literature considering it as similar to task conflict (Behfar, Mannix, Peterson, &Trochim, 2011;Kuriakose, S.S, Jose, M.R.A,& Jose,2019 b;Greer & Jehn, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such conflicts over goals, processes and personality differences are termed as task conflict, process conflict and relationship conflict respectively (Jehn, Greer, Levine, & Szulanski, 2008;Vaux& Kirk, 2018). Previous studies have reiterated that conflicts over personality and value differences which are termed as -relationship conflicts are detrimental for individuals and organisations alike (Hagemeister & Volmer, 2018;Ismail, Richard, & Taylor, 2012;Volmer, 2015;Li et al, 2020). However, in the conflict research, studies differ about the effect of task conflict on employee well-being and process conflict have been omitted from conflict literature considering it as similar to task conflict (Behfar, Mannix, Peterson, &Trochim, 2011;Kuriakose, S.S, Jose, M.R.A,& Jose,2019 b;Greer & Jehn, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current study adopted this model partially to develop the conceptual model of the association between conflicts and employees' intention to leave from the organization. Based on the research findings, researchers found that there is a connection between negative moods and positive moods to the impact the level of relationship conflicts experienced by subordinates (Ismail et al, 2012). Subordinates' collectivism values support to strengthen the positive moods or negative moods interaction on relationship conflicts.…”
Section: Theoretical Model Introduced For Relationship Conflicts and mentioning
confidence: 91%
“…Social ties (CL Wang, HFL Chung 2013) unlike previous studies which commonly tackles it from the weak and strong ties perspective, here refers to both the business and political ties normally considered by scholars as managerial ties (K.M. Ismail et al, 2012). Existing literature contribute more to the social Networks at the organizational level (macro) other than Individual level (micro).…”
Section: Introductionmentioning
confidence: 99%